Perbandingan dua aplikasi penapis fibrilasi atrium berbasis ponsel cerdas pada populasi Indonesia - Tondas, Alexander Edo; Halim, Rolando Agustian; Felani, Muhammad Rizki; Caesarani, Fianirazha Primesa; Puspita, Indah; Toruan, Mangiring Lumban (The Indonesian Heart Association, 2021)
Background: Due to its adverse outcomes and thromboembolic complications, early detection of atrial fibrillation (AF) is advisable in the general population. This study aims to compare the diagnostic ability of two distinct method in smartphone application format, namely : AliveCor KardiaMobile and FibriCheck. Methods: This study was conducted in Mohammad Hospital General Hospital Palembang with convenience sampling of 170 participants aged 18 years or older. The subjects underwent Fibricheck and KardiaMobile recordings followed by 12 lead electrocardiogram read by board-certified cardiologist as the diagnostic standard. Results: After the exclusion of previous pacemaker implantation (n=7), 163 patients were included in the study. The mean age was 51±15 years with gender distribution of 74.8% men and 25.2% women. Most of the subjects were asymptomatic (87.1%) with mean blood pressure of 130/80 mmHg. The Fibricheck readings showed sensitivity of 73% and specificity of 93%, meanwhile Kardiamobile was able to detect AF with sensitivity of 77% and specificity of 98%. Conclusion: In our study, KardiaMobile demonstrated overall greater sensitivity and specificity when compared to FibriCheck. However, KardiaMobile requires an external metal sensor that must be puchased separately. To the best of our knowledge, this is the first study to directly compare both methods in the Indonesian population.